2004
DOI: 10.1104/pp.104.041269
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Enzymes Exhibiting β-d-Xylosidase Activities in Stem Tissues of Arabidopsis

Abstract: This work describes the purification and characterization of enzymes that exhibit b-D-xylosidase activity in stem tissues of Arabidopsis. This is the first detailed investigation that concerns the characterization of catalytic properties and sequence identity of enzymes with b-D-xylosidase activities in a dicotyledonous plant. Three different enzymes, ARAf, XYL4, and XYL1 with apparent molecular masses of 75, 67, and 64 kD, respectively, were purified to homogeneity. ARAf was identified as a putative a-L-arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 67 publications
6
129
0
1
Order By: Relevance
“…There is no correlation between substrate specificities and the primary structure of the enzyme, suggesting the necessity of biochemical properties when using enzyme annotations in a database. Minic et al (2004Minic et al ( , 2006 showed that several β-xylosidase and α-Larabinofuranosidase from Arabidopsis possessed similar substrate specificities against both arabinan and arabinoxylan and suggested that these broad substrate specificities are rather convenient for modification of the complex cell wall structure. On the other hand, α-L-arabinofuranosidase isolated from Japanese pear showed limited activity of releasing arabinose from pectic arabinan (Tateishi et al, 2005a).…”
Section: Substrate Specificity Of α-L-arabinofuranosidasementioning
confidence: 99%
See 1 more Smart Citation
“…There is no correlation between substrate specificities and the primary structure of the enzyme, suggesting the necessity of biochemical properties when using enzyme annotations in a database. Minic et al (2004Minic et al ( , 2006 showed that several β-xylosidase and α-Larabinofuranosidase from Arabidopsis possessed similar substrate specificities against both arabinan and arabinoxylan and suggested that these broad substrate specificities are rather convenient for modification of the complex cell wall structure. On the other hand, α-L-arabinofuranosidase isolated from Japanese pear showed limited activity of releasing arabinose from pectic arabinan (Tateishi et al, 2005a).…”
Section: Substrate Specificity Of α-L-arabinofuranosidasementioning
confidence: 99%
“…Hence, the expression pattern of family 3 α-L-arabinofuranosidase described below was also summarized including β-xylosidase and putative α-L-arabinofuranosidase/β-xylosidase. cDNA clones of the enzymes were isolated from barley (Lee et al, 2003), tomato (Itai et al, 2003), Arabidopsis (Goujon et al, 2003;Minic et al, 2004Minic et al, , 2006, Japanese pear (Tateishi et al, 2005a), radish (Raphanus sativus) (Kotake et al, 2006), peach (Hayama et al, 2006), strawberry (Bustamante et al, 2006), and alfalfa (Medicago sativa) (Xiong et al, 2007). They constitute a small gene family and the expression of each isozyme was found in various organs and developmental stages.…”
Section: Expression Pattern Of α-L-arabinofuranosidasesmentioning
confidence: 99%
“…AtBXL1 was found to encode a bi-functional β-xylosidase/α-arabinofuranosidase, which is expressed throughout the plant including the developing seed. [39][40][41] Chemical analysis of extracted mucilage indicated increases in α-1-5 linked arabinans, a neutral side chain on the main pectic component RG I. 41 Immunofluorescence on sectioned MSCs also indicated an increase of α-1-5 linked arabinans in the primary cell walls.…”
Section: 36-38mentioning
confidence: 99%
“…AtAraf51A was reported as a bifunctional enzyme which possessed a-L-arabinofuranosidase/b-Dxylosidase activity in the previous report (Minic et al 2004). However, our results clearly indicated that the recombinant AtAraf51A hydrolyzed PNP-a-Larabinofuranoside but did not hydrolyze any other PNPglycosides including PNP-b-D-xyloside.…”
Section: Substrate Specificity Of Ataraf51amentioning
confidence: 99%
“…The expression of the gene is intense in zones of cell proliferation, developing and regressing floral tissues, floral abscission zones, and the vascular system (Fulton and Cobbett 2003). The gene product seemed to act on polysaccharides at the plant cell wall, and play an important role for cell wall modification (Minic et al 2004). Analysis of sugar composition of transgenic A. thaliana plants and immunolocalization patterns proposed that arabinans are potential in vivo substrates of the enzyme (Montes et al 2008).…”
mentioning
confidence: 99%